Acute Liver Toxicity Modifies Protein Expression of Glutamate Transporters in Liver and Cerebellar Tissue - Jiménez-Torres, Catya; El-Kehdy, Hoda; Hernández-Kelly, Luisa C.; Sokal, Etienne; Ortega, Arturo; Najimi, Mustapha (Frontiers in Neuroscience, 2021)
Glutamate is the main excitatory amino acid acting at the level of pre and postsynaptic neurons, as well as in glial cells. It is involved in the coordinated modulation of energy metabolism, glutamine synthesis, and ammonia detoxification. The relationship between the functional status of liver and brain has been known for many years. The most widely recognized aspect of this relation is the brain dysfunction caused by acute liver injury that manifests a wide spectrum of neurologic and psychiatric abnormalities. Inflammation, circulating neurotoxins, and impaired neurotransmission have been reported in this pathophysiology. In the present contribution, we report the effect of a hepatotoxic compound like CCl4 on the expression of key proteins involved in glutamate uptake and metabolism as glutamate transporters and glutamine synthetase in mice liver, brain and cerebellum. Our findings highlight a differential expression pattern of glutamate transporters in cerebellum. A significant Purkinje cells loss, in parallel to an up-regulation of glutamine synthetase, and astrogliosis in the brain have also been noticed. In the intoxicated liver, glutamate transporter 1 expression is up-regulated, in contrast to glutamine synthetase which is reduced in a time-dependent manner. Taken together our results demonstrate that the exposure to an acute CCl4 insult, leads to the disruption of glutamate transporters expression in the liver-brain axis and therefore a severe alteration in glutamate-mediated neurotransmission might be present in the central nervous system.